The Impact of Acute Hydration on Body Composition Assessment Using the Bioelectrical Impedance Method in Female Pilates Novices - Lejla Dizdarević; Saša Vuk (Journal of Anthropology of Sport and Physical Education)
The aim of this study was to examine the impact of acute hydration on body composition assessment using the bioelectrical impedance (BIA) method. Given the sensitivity of BIA measurements to changes in hydration status, it was examined how the intake of 0.5 l of water affects body mass and body fat percentage and how quickly the values stabilize after hydration. The study was conducted on 28 female subjects who are recreationally involved in Pilates, and measurements were performed in the morning on an empty stomach, using a multi-purpose BIA device. Body mass and fat percentage were assessed four times: twice before hydration and five and fifteen minutes after hydration. The results showed a statistically significant increase in body mass immediately after water intake (p < 0.001), while body fat percentage also increased, contrary to expectations. The values stabilized within 15 minutes after hydration. These changes can be explained by the redistribution of fluid in the body and the algorithms that BIA devices use to assess body composition. It is concluded that fluid intake immediately before BIA analysis may temporarily affect the results, which may lead to misinterpretations of body composition. It is recommended to standardize the measurement conditions and conduct testing under the same hydration conditions to ensure greater reliability of body composition assessment.